Deciphering QS. al-Maidah: 51 in Qur'an, Liberation & Pluralism: Analyzing the Interpretation of the Word Auliya' through Farid Esack's Perspective - Ummam, Naufa Izzul; Haris, Abdul (Journal of Islamic Civilization, 2023)
The interpretation of the term "leader" in reference to "auliya'" mentioned in Qs. al-Maidah: 51 has been a topic of debate among Indonesian Muslim scholars. In contrast to Farid Esack, who appears to lack understanding regarding the definition of leadership as it pertains to this verse, his focus remains firmly fixed on issues more relevant to the South African context. This study endeavors to propose Farid Esack's interpretation of the term auliya' in Qs. al-Maidah: 51, as it pertains to the South African context. Specifically, it examines his exploration of the word's meaning and delves into the implications of his unique perspective. This goal can be used as an alternative to other interpretations related to the word auliya' in Qs. al-Maidah. 51: 51. The research is a qualitative research with literature data which is analysed descriptively. The main data in this research is the meaning of the word auliya' in the book Qur'an Liberation & Pluralism by Farid Esack. The analysis of Esack's meaning presentation is conducted by examining the literature by revisionist mufassirs. The findings of this investigation conclude that Farid Esack, based on his liberation hermeneutics, interprets the term auliya to connote collaboration and solidarity. The implication of Esack's interpretation is that it is impermissible for a Muslim to collaborate with non-Muslims unless he does not forsake Muslims, intends to safeguard believers, has entered into a peace treaty with believers, and refrains from fighting against them. When contextualized within South Africa, Esack contends that a believer can cooperate with non-Muslims if it promotes the well-being of Muslims and combats racist conduct, oppression and injustice. However, to ascertain the pertinence of utilizing these interpretations within the Indonesian context, additional research is imperative. This study solely focuses on scrutinizing the outcomes and consequences of Esack's interpretation.